Analysis of Hemodialysis Service Unit Development in Sri Pamela Hospital Tebing Tinggi - Armaya, Dita; Ginting, Chrismis Novilda; Napiah, Ali (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Indonesia currently following the global non-communicable disease trend, such as the growth of chronic kidney disease and end-stage kidney disease numbers. In the last eight years, the number of end-stage kidney disease patients jumped from 9.649 to 66.433 (2010-2018). One of the consequences of this increasing incidence is the increasing need for kidney replacement therapy, one being hemodialysis. Strength-Weakness-Opportunity-Threat (SWOT) analysis in a common business tool used to assess and evaluate the feasibility of business development and/or expansion. This study aims to assess the potential of the development of a hemodialysis unit in Sri Pamela Tebing Tinggi Hospital. This study is an analytical descriptive evaluation study. Data in this study was gathered from three key informants (nephrologist-in-charge, head of the hemodialysis unit, and hemodialysis nurse) and two additional informants (regular hemodialysis patients) in Sri Pamela Tebing Tinggi Hospital. Data gathered from this study was analyzed using Internal-External (IE) and SWOT matrix. This study discovers that the existing hemodialysis unit in Sri Pamela Tebing Tinggi Hospital stands on the first quadrant of the IE matrix, grows and is built with vertical integration, and is at S-O strategy in the SWOT matrix.  According to these findings, it can be concluded that the Sri Pamela Tebing Tinggi Hospital's hemodialysis unit has great potential for further development by expanding its service capacity by expanding its building, adding more hemodialysis machines along with more manpower. Keywords: ESRD, Hemodialysis, Hospital Management, SWOT